Luis Villoro and Markus Gabriel facing scientism still present in the 21st century - FERREIRA GONZÁLEZ, Jesús (Utopía y Praxis Latinoamericana, 2023)
Our thesis is that Villoro's philosophy is still valid to think about the problem of scientism. This conclusion is drawn as a result of putting into play the ideas of the Mexican philosopher based on the reflection that Markus Gabriel has made in this regard from the new realism. As a result of our research, we have found that both philosophers coincide in their criticism of scientism and in the alternative they propose against it. For both, scientism is an ideology that dehumanizes the knowledge of humanity, in which the perspective of the natural sciences prevails methodologically over the social sciences. Faced with this problem, both authors propose the autonomy and liberation of the sciences of the spirit; likewise, that science, although it is distinguished from wisdom, is not disassociated from the meaning and value of human existence and reality (field of the spirit).